Agronomical, physiological and biochemical approaches to characterize sweet sorghum genotypes for biofuel production - Subramanian, Satheesh K. (Kansas State University, 2013)
Sweet sorghum (Sorghum bicolor L. Moench) is an important bioenergy crop. There is a wide array of genetic diversity in sweet sorghum germplasm collections. However, information on traits associated with sugar yield, optimum harvesting time for maximum sugar yield, effects of abiotic stresses on sugar yield is scarce. The objectives of the present study were: to identify traits that are associated with sugar yield, to determine the optimum harvesting time for maximum sugar yield and to understand the physiological responses of different sweet sorghum genotypes to drought and high temperature. In order to meet these objectives, five independent field and greenhouse studies were conducted. Field experiments were conducted using 280 sweet sorghum germplasm and were evaluated for 2 years. From this study, 30 genotypes representing high and low sugar yielders were selected for the subsequent experiment. We observed a significant variation in physiological, morphological and sugar yield traits associated with biofuel production. In the selection experiment, investigations on the morphological, physiological attributes helped to identify those characters which influence or limit sugar yield in the sweet sorghum. Another field study was conducted to optimize the harvesting time for obtaining highest sugar and juice yields in sweet sorghum. Sweet sorghum variety M81E was harvested at ten growth stages. Our results suggest that the optimum time for harvesting of sweet sorghum cultivar M81E is between milk and hard dough stages when highest sugar yield was observed. Studies on different levels of water stress were studied under greenhouse conditions. Four sweet sorghum genotypes (Awanlek, Smith, Tracy and Wray) were subjected to three water stress treatments (100% pot capacity (PC); 70% PC and 30% PC) for 20 days at early seed filling (Milk) stage. The results showed that genotypes differed significantly for all growth and yield, biochemical and physiological traits. Severe water stress significantly decreased juice and sugar yields by decreasing net photosynthetic rate, transpiration rate, stomatal conductance and sucrose content in the stem juice. Genotypes Tracy and Wray produced significantly highest brix, stem fresh weight, juice and sugar yield under both irrigated and water stress conditions. In another greenhouse study, we quantified the effects of drought, high temperature, and their combinations on growth, physiology and yield of sweet sorghum genotypes. The same four genotypes above were subjected to four treatments, T1 - control, T2 - drought stress, T3 - high temperature stress and T4 - combination of drought and high temperature for 16 days after anthesis. The result showed that significant difference was observed for growth and yield traits, physiological traits and non-reducing and total sugar content in juice for genotypes and treatments. Among the genotypes Tracy recorded higher juice and sugar yield. Among the various treatments, combination of drought and high temperature was found to be more deleterious in reducing most of the biofuel traits followed by drought and high temperature stress. The above studies gave significant findings with regards to the identification of superior sweet sorghum germplasm, their tolerance capacity to different abiotic stresses, which allows better selection for the use of bioenergy production.
Keywords: Sweet sorghum; Drought stress; Harvest timing; Juice yield; Brix; Agronomy (0285)